Nickel exposure promotes osmoregulatory disturbances in Oreochromis niloticus gills: histopathological and energy dispersive spectrometry analysis - Marcato, A. C. C. [UNESP]; Yabuki, A. T. [UNESP]; Fontanetti, C. S. [UNESP] (Springer, 2014)
Water is an essential factor for maintaining the vital functions of living beings. Nickel is the 24th most abundant element on Earth; it is a heavy metal that is genotoxic and mutagenic in its chloride form. Due to industrial use, its concentration in surface sediments increased considerably. Fish develop characteristics that make them excellent experimental models for studying aquatic toxicology. They are particularly useful because they can alert of the potential danger of chemical substances or environmental pollution. Due to water quality impairment and because there are few published studies that relate nickel to tissue alteration, this study aimed to examine the consequences of nickel in an aquatic environment. For this analysis, individuals of Oreochromis niloticus were exposed for 96 h to three different concentrations of nickel dissolved in water according to the standard established by Brazilian law and compared them to a control group. After exposure, the gills were analyzed using X-ray microanalysis, ultramorphology, and histological and histochemical analysis. The results demonstrated that all the concentrations used in the experiment altered the histophysiology of the individuals exposed. In conclusion, the nickel presents a toxic potential to fish, even at the lowest concentration tested, which is equivalent to half of the concentration allowed by law. The CONAMA resolution should be revised for this parameter because of the interference of this metal in the histophysiology of the tested organism.
Keywords: Histopathology; Mucous cells; Water pollution; Heavy metals; Bioindicator; Freshwater fish